Impression Techniques on the Management of Fibrous Maxillary Ridge - Ang, Yee; Tew, In Meei; Goo, Chui Ling (Indonesia Prosthodontic Association, 2021)
Fibrous or flabby ridges on the edentulous maxillary arch are commonly found in combination syndrome or due to ill-fitting dentures. The main challenge in complete denture fabrication for these cases is the likelihood of displacing the mobile tissue from its resting position due to the forces exerted during impression taking. In this case report, two patients complained of ill-fitting maxillary complete dentures despite multiple adjustments. Upon intraoral examination, the patients presented with moderately to severely displaced flabby ridge on the premaxilla region. As both the patients are medically compromised and denied any surgical treatment, flabby ridges were conservatively managed using two modified impression techniques in fabrication of maxillary complete dentures. A single-step impression technique with simultaneous use of light and medium body silicone impression materials was utilized. It requires high clinical skills but offers a simple and least time-consuming approach in recording the surface details of severely displaced flabby ridge. A two-step technique records normal tissues and flabby ridges using zinc oxide eugenol (ZOE) and light body silicone impression materials respectively in sequence. This technique enables good control over the volume and flow of light body silicone as compared to single-step technique, but precautions should be taken to avoid custom tray misplacement during the second stage of impression taking. Custom trays were designed differently in both techniques, especially on the timing of tray perforations and handle position to further ease the impression making process. Both the dentures were delivered with good support, stability, and retention. The patients were satisfied with the outcome. In a nutshell, simplified solutions are recommended in this case report for clinicians with different levels of competence. A single custom tray with perforations and extra spacers is recommended as the most cost-effective manner to reduce the complexity of the procedure.